Biomass and central receiver system (CRS) hybridization: Integration of syngas/biogas on the atmospheric air volumetric CRS heat recovery steam generator duct burner - Bruno Coelho (2015)
Central receiver systems (CRS) are a promising concentrated solar power (CSP) technology for dispatchable electricity generation. The CRS levelized cost of electricity (LCOE) is usually increased by low power-block capacity factors or by high thermal storage costs. The economical turnover is still positive for the Portuguese case but depends on the bonus feed-in tariffs. On the other hand, with biomass existing feed-in tariffs and raising prices, the viability of current biomass power plants is at risk. To address these issues, several base case power plants and hybrid biomass/CSP options are analyzed: wood gasification, refuse-derived fuel pellets, biogas from a wastewater anaerobic digester, biogas from a landfill and natural gas. The solution with lower LCOE was obtained for the hybridization of a 4 MWe CRS using an atmospheric volumetric receiver with biogas from an anaerobic digester using sludge from a wastewater treatment plant (WWTP). Different results would be obtained for the hybrid systems if different CRS technologies are used. The hybrid CRS/anaerobic digester power plant LCOE is 0.15 V/kWh, returning the investment in 13 years (assuming sludge collection and transport without cost) with the best net present value (15 million euro) and internal rate of return of all the hybrid options